Juridical Analysis of Abolition Marriage Ban with the Same Workplace: MK 13 / PUU-XY / 2017 - Khayatudin, Khayatudin; Utomo, Merdiko Nur (Prosiding Seminar, 2020)
The purpose of this study finds out the basis for the judge's consideration in granting a lawsuit over the prohibition of workers from having marital in one workplace. Research method used normative juridical research approach, it is concluded that decision of the Mahkamah Konstitusi (MK) Number 13 / PUU-XV / 2017 had permanent and binding legal force. MK granted the petitioner namely the Labor Law Pasal 153 Paragraph (1) letter f that it contradicted the 1945 Constitution and also the Law on Marriage and the Law on Human Rights where a person's constitutional rights form a family and continue the descent through a legal marriage